1969
DOI: 10.1103/physrevlett.22.1433
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Transition in the Electronic Nature of Solids

Abstract: Striking evidence for a fundamental covalent-ionic transition in the electronic nature of solids is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
167
2
5

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(179 citation statements)
references
References 20 publications
5
167
2
5
Order By: Relevance
“…All such treatments should lead to a different reactivity at the interface and therefore to different barrier heights and leakage currents. Fermi level pinning is a well known phenomenon for semiconductor interfaces, which is particularly pronounced for covalently bonded semiconductors like Si or III-V compounds [46]. The Fermi level pinning is related to induced gap states, which occur at semiconductor interfaces due to the wave function matching leading to an exponentially decaying wave function in the semiconductor energy gap [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…All such treatments should lead to a different reactivity at the interface and therefore to different barrier heights and leakage currents. Fermi level pinning is a well known phenomenon for semiconductor interfaces, which is particularly pronounced for covalently bonded semiconductors like Si or III-V compounds [46]. The Fermi level pinning is related to induced gap states, which occur at semiconductor interfaces due to the wave function matching leading to an exponentially decaying wave function in the semiconductor energy gap [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…However, the generally accepted value is about 1.08 eV [31]. Kurtin et al [32] suggested that the Schottky barrier height on GaN should depend directly on the work function or electronegativity difference between the metal electrode and GaN. Foresi and Moustakas [33] observed this direct correlation experimentally, while Guo et al [34] and Mori et al [35] observed only a weak dependence of the Schottky barrier height on the metal work function for n-type GaN and p-type GaN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, the experimental and theoretical studies performed up to now (Bardeen-like) and ionic (Schottky-like) [20] junctions, as the differentiation made by Andrews and Phillips [12] in terms of the strength of the interface bonds, could be described by the relaxation at the interface [10] [3,8], whereby the properties of the junction are explained in terms of the dipole layer built up at the interface. According to this theory the barrier height for a n-type junction (cphn) can be written as ( Fig.…”
mentioning
confidence: 97%
“…The parameter A is in fact similar to the one introduced by Mele and Joannopoulos [10] to describe the broadening of the dangling bond states which they assume to appear in the metal-semiconductor junction. (19) and (20) (15) and (16). Equation (22) gives q' as a function of e-note the dependence of cp on B.…”
mentioning
confidence: 99%
See 1 more Smart Citation